2016
DOI: 10.1186/s12933-016-0458-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum calcium and heart failure with preserved ejection fraction in patients with type 2 diabetes

Abstract: BackgroundType 2 diabetes mellitus (T2DM) is a recognized trigger factor for heart failure with preserved ejection fraction (HFpEF). Recent studies show that higher serum calcium level is associated with greater risk of both T2DM and heart failure. We speculate that increased serum calcium is related to HFpEF prevalence in patients with T2DM.MethodsIn this cross-sectional echocardiographic study, 807 normocalcemia and normophosphatemia patients with T2DM participated, of whom 106 had HFpEF. Multinomial logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…The 28 selected studies included a wide range of potential novel diagnostic HFpEF circulating biomarkers ( Table 1 ). 22–49 …”
Section: Resultsmentioning
confidence: 99%
“…The 28 selected studies included a wide range of potential novel diagnostic HFpEF circulating biomarkers ( Table 1 ). 22–49 …”
Section: Resultsmentioning
confidence: 99%
“…First, hyperglycemia promotes anaerobic myocardial metabolism, inhibits production of nitric oxide and increases the production of reactive oxygen species in endothelial and vascular smooth muscle cells, thus impairing endothelial function [ 42 , 43 ]. Second, hyperglycemia alters cardiac structure through post-translational modification of extracellular matrix, both leading to impaired relaxation and increased ventricular stiffness and alters calcium metabolism [ 44 48 ]. Finally, insulin deficiency is associated with increased lipolysis and excess circulating free fatty acids, which are toxic to ischemic myocardium and were shown to be associated with the development of arrhythmias [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we first found that there was an independent association between higher corrected serum calcium levels and the increased risk of in-hospital HF in AMI population. In prior studies, higher serum calcium was independently related to HF risk in a community-based cohort study ( 11 ), and elevated serum calcium levels were an independent risk factor for HFpEF in patients with type 2 diabetes mellitus (T2DM) ( 29 ). Some potential mechanisms may contribute to the association.…”
Section: Discussionmentioning
confidence: 99%